Assessing the role of ketogenic dietary therapy in ring chromosome 20 syndrome: A patient‐led approach. Issue 2 (11th March 2020) - Gordon, Donald; Watson, Allison; Desurkar, Archana; Cowley, Laura; Hiemstra, Thomas F.
Abstract: Ring chromosome 20 syndrome (r(20)) is an ultra‐rare disease characterized by drug‐refractory epilepsy, cognitive impairment, and behavioral problems. Nonpharmacological treatments alongside antiepileptic drugs early after diagnosis may help reduce seizure frequency and preserve cognition. Ketogenic dietary therapy (KDT) has benefitted children with complex, refractory epilepsies, but its efficacy in r(20) is unknown. We assessed clinical prescription, implementation, and patient experience of KDT in r(20) through online surveys and a workshop. Forty‐two patients, families, carers, and 23 healthcare professionals completed the surveys. While nearly all patients were familiar with KDT, only half had tried it. Significant improvement in seizure activity, cognition, and alertness was reported; side effects were typically mild but with one report of increased seizure frequency. A high rate of co‐morbidity, older age at presentation, behavioral problems, and cognitive impairment can make implementing KDT in r(20) challenging. In the UK, NHS KDT services are predominantly available to pediatric patients, with very limited adult access. A health economic analysis illustrating reduced acute care costs or improved quality of life may support more widespread KDT implementation. Growing evidence supports KDT as an effective and safe intervention, but further research is needed to understand the mechanisms of r(20) and its interaction with ketosis.